Evaluation of Verteporfin as a Novel Antifibrotic Agent in a Rabbit Model of Glaucoma Filtration Surgery - Michelle T. Sun, MBBS, PhD; Renee M. Cotton, VMD; Chaow Charoenkijkajorn, MD; Julian Garcia-Sanchez, MD; Roopa Dalal, MSc; Xin Xia, MD, PhD; Jonathan H. Lin, MD, PhD; Kuldev Singh, MD; Jeffrey L. Goldberg, MD, PhD; Wendy W. Liu, MD, PhD (Ophthalmology Science, 2024)
Purpose: Verteporfin is a benzoporphyrin derivative which is Food and Drug Administration-approved for treatment of choroidal neovascularization in conjunction with photodynamic therapy. It has been shown to prevent fibrosis and scar formation in several organs and represents a promising novel antifibrotic agent for glaucoma surgery. The goal of this study is to determine the effect of verteporfin on wound healing after glaucoma filtration surgery. Design: Preclinical study using a rabbit model of glaucoma filtration surgery. Subjects: Eight New Zealand white rabbits underwent glaucoma filtration surgery in both eyes. Methods: Eyes were randomized into 4 study groups to receive a postoperative subconjunctival injection of 1 mg/mL verteporfin (n = 4), 0.4 mg/mL mitomycin C (MMC; n = 4), 0.4 mg/mL MMC + 1 mg/mL verteporfin (n = 4), or balanced salt solution (BSS) control (n = 4). Bleb survival, vascularity, and morphology were graded using a standard scale over a 30-day period, and intraocular pressure (IOP) was monitored. At 30 days postoperative or surgical failure, histology was performed to evaluate for inflammation, local toxicity, and scarring. Main Outcome Measures: The primary outcome measure was bleb survival. Secondary outcome measures were IOP, bleb morphology, and bleb histology. Results: Compared to BSS control blebs, verteporfin-treated blebs demonstrated a trend toward increased surgical survival (mean 9.8 vs. 7.3 days, log rank P = 0.08). Mitomycin C-treated blebs survived significantly longer than verteporfin-treated blebs (log rank P = 0.009), with all but 1 MMC-treated bleb still surviving at postoperative day 30. There were no significant differences in survival between blebs treated with combination verteporfin + MMC and MMC alone. Mitomycin C-treated blebs were less vascular than verteporfin-treated blebs (mean vascularity score 0.3 ± 0.5 for MMC vs. 1.0 ± 0.0 for verteporfin, P < 0.01). Bleb histology did not reveal any significant toxicity in verteporfin-treated eyes. There were no significant differences in inflammation or scarring across groups. Conclusions: Although verteporfin remained inferior to MMC with regard to surgical survival, there was a trend toward increased survival compared with BSS control and it had an excellent safety profile. Further studies with variations in verteporfin dosage and/or application frequency are needed to assess whether this may be a useful adjunct to glaucoma surgery. Financial Disclosure(s): Proprietary or commercial disclosure may be found in the Footnotes and Disclosures at the end of this article.